Prevalence and Plasmodium species distribution of asymptomatic malaria parasitemia among blood donors at the Lilongwe blood transfusion center - Bowa, Collins; Kalonga, Ndagha; Mbonshi, Benjamin; Sitali, Lungowe; Simwela, Joseph; Kudowa, Evarister; Tepeka, Amazing-Grace (Frontiers in Malaria, 2025)
BackgroundBlood transfusions are vital for treating anemia, yet in malaria-endemic regions such as Malawi, the risk of infection transmission remains significant. Owing to constrained resources and infrastructure, many blood centers have inadequate capacity for malaria detection, leading to the absence of routine screening protocols. This study aimed to explore the prevalence of asymptomatic malaria parasitemia, identify Plasmodium species, and investigate associated factors among blood donors at the Lilongwe Centre of the Malawi Blood Transfusion Service (MBTS).MethodsThis study employed a cross-sectional research design conducted at the Lilongwe Branch of the Malawi Blood Transfusion Service, a pivotal center for blood collection and distribution in Malawi’s central region. The research focused on a population of voluntary asymptomatic blood donors who presented themselves at designated donation centers. The prevalence of asymptomatic malaria parasitemia was determined using two methods: Plasmodium falciparum histidine-rich protein 2 (PfHRP2) rapid diagnostic tests (RDTs) for detecting Plasmodium falciparum parasites and microscopic analysis for confirmation and identification of other Plasmodium species, along with density quantification. Identification of factors associated with malaria transmission among blood donors was done using structured questionnaire. The study was conducted over a two-week period at the MBTS, with data analysis performed using R version 4.3.1, with statistical significance set at p-value < 0.05.ResultsThe study identified an overall malaria prevalence of 13.5% (51/377) among the participants, with 13.4% (9/67) of females and 13.5% (42/310) of males testing positive. Of the positive cases, 85.4% (41/48) were due to Plasmodium falciparum, 8.3% (4/48) were mixed infections of Plasmodium falciparum and Plasmodium malariae, and 6.3% (3/48) were solely Plasmodium malariae. Significant demographic factors influencing species distribution included age, occupation and residence. Other significant factors were blood group, repellent use, and travel history. A multivariate logistic regression model was used, but no significant associations were identified at the 0.05 significance level.ConclusionThe detection of a substantial burden of asymptomatic malaria parasitemia among blood donors highlights a potential risk for transfusion-transmitted malaria in Malawi. This finding underscores the urgent need to strengthen malaria screening protocols and diagnostic capacity within blood transfusion services.